THE IMPORTANCE OF ECONOMIC EDUCATION: EMPOWERING INDIVIDUALS FOR FINANCIAL LITERACY AND ECONOMIC SUCCESS - Navruzbayeva Gavhar Bakhtiyar qizi (Zeta Repository, 2023)
This article explores the importance of economic education in empowering individuals with the knowledge, skills, and mindset necessary to understand and participate in the economy effectively. It highlights the benefits of economic education, including enhanced financial literacy, critical thinking and problem-solving skills, global awareness, practical application of economic concepts, and promotion of economic justice and equity. The article emphasizes the role of economic education in equipping individuals for economic success and fostering a more just and sustainable economic system.